The Influence of an Exogenous Microbial Enzyme Supplement on Feed Consumption, Body Growth and Follicular Development of Pre-Lay Pullets on Maize-Soy Diets - Chauynarong, N.; Iji, P.A.; Isariyodom, S.; Mikkelsen, L. (International Journal of Poultry Science, 2008)
An experiment was conducted to examine the benefits of supplementing maize-soy diets with a composite microbial enzyme, Allzyme SSF, for laying hens at the pullet stage. Seven hundred and twenty 12-week old Isa Brown pullets were used in the different level of protein content diets. Feed intake from 12 to 16 weeks of age was unaffected by the enzyme supplement, except at the lowest protein content (P<0.05). Feed intake was, however, affected by the enzyme supplement between 16 and 20 weeks (P<0.001) and over the entire trial period (P<0.05). Body weight at 16 weeks of age was reduced (P<0.05) on the control low-protein diet. Feed conversion ratio was not affected by dietary protein content or through supplementation with the microbial enzyme. The relative weight of the ovary was reduced (P<0.01) on the low protein control diet, but the weight of visceral organs associated with digestion was not affected. The pullets in all groups failed to come into lay at 17 weeks of age, mainly due to very severe winter, as the experiment was conducted in a house that was not completely temperature-controlled. Onset of lay occurred from about 23 weeks of age, after the hens were already on a commercial diet but effects of previous dietary treatments on early egg production were noticeable.